STRATEGI KOMUNIKASI HUMAS POLRESTA PEKANBARU DALAM MENGINFORMASIKAN KASUS BEGAL KEPADA MASYARAKAT - Azura, Nur; Sari, Genny Gustina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Begal is included in cases of violent theft, theft with violence using sharp weapons, theft with weighting and theft of motorized vehicles. The stiffness that was initially carried out by adults has now been carried out by teenagers. The high incidence of crime has led to problems in getting special treatment from the police, because crime often endangers the victims, it is not uncommon for victims of casualties to have accidents trying to fight, some cases recorded at Pekanbaru Police, victims of at least injuries to the body and some cases also causes death. This study aims to determine the strategy of selecting communicators, audience selection strategies, message formulation strategies and media selection strategies in informing begal cases to the public.This study uses qualitative research methods with descriptive approach. The research subjects consisted of eight people who were selected using a purposive technique. Data collection is done through interviews, observation and documentation. To test the validity of the data the author used the method of extending participation and triangulation.The results of this study indicate that the Communicator's Communicator Selection Strategy for Pekanbaru Police in Informing Begal Cases in Pekanbaru City is to choose communicators based on criteria that have been determined by Pekanbaru Police Public Relations. Such as: Having closeness with audiences, Having similarities and social attractiveness, Similarity is another important factor that influences the message delivery by the public, Known for its accessibility and authority, Smart in how to convey messages and Known status, power and authority. The Strategy for Selecting Audiences is that of the Pekanbaru City community as a whole, especially the quiet areas that are usually the place where the settlement occurs. Message Compilation Strategy is by making a message that is easily remembered by the community. Media selection strategy is to choose to use Social Media, namely Instagram social media and Facebook.Keywords: Communication Strategy, Public Relations, Begal